Put conservation into practice - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
The Conservation Handbook: Research, Management and Policy By WJ Sutherland, Blackwell Science, UK. 2000. 296 pp. ISBN 0632053445 GBP 24.99 Euro 41.70